2020
DOI: 10.3390/ijms21072262
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Strategies for Retinal Ganglion Cell Degeneration: Current Status and Challenges Ahead

Abstract: The retinal ganglion cells (RGCs) are the output cells of the retina into the brain. In mammals, these cells are not able to regenerate their axons after optic nerve injury, leaving the patients with optic neuropathies with permanent visual loss. An effective RGCs-directed therapy could provide a beneficial effect to prevent the progression of the disease. Axonal injury leads to the functional loss of RGCs and subsequently induces neuronal death, and axonal regeneration would be essential to restore the neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 313 publications
0
44
0
1
Order By: Relevance
“…Furthermore, mice carrying a heterozygous deletion of the BDNF gene were not protected by exercise. Other neurotrophins, including neurotrophic growth factor (NGF) and insulin-like growth factor-1 (IGF-1), have demonstrated neuroprotective effects on retinal ganglion cells [ 32 , 33 ]. However, their roles in exercise-mediated protection are less established.…”
Section: Targeting Exercise For Neuroprotection In Glaucomamentioning
confidence: 99%
“…Furthermore, mice carrying a heterozygous deletion of the BDNF gene were not protected by exercise. Other neurotrophins, including neurotrophic growth factor (NGF) and insulin-like growth factor-1 (IGF-1), have demonstrated neuroprotective effects on retinal ganglion cells [ 32 , 33 ]. However, their roles in exercise-mediated protection are less established.…”
Section: Targeting Exercise For Neuroprotection In Glaucomamentioning
confidence: 99%
“…Animal studies involving either induced (e.g., microbead occlusion, [10]) or genetic (e.g., DBA/2J and GC-1 −/− mice [10][11][12]) elevations in IOP have proven invaluable in identifying key molecular events in RGC dysfunction, which highlight an early window of neuroprotective opportunity. Ideally, neuroprotective strategies should prevent RGC dysfunction and thus subsequent degeneration while promoting repair or even regeneration of damaged tissue to restore vision, as reviewed elsewhere [13]. While clinical neuroprotective trials have proven difficult [14], therapies involving growth factors may have the potential to achieve those goals.…”
Section: Early Glaucoma: Strategies To Protect Rgcsmentioning
confidence: 99%
“…Despite the known role of VEGF in neovascularization (Folk and Stone, 2010), it has been shown that VEGF treatment reduces apoptosis in models of glaucoma whereas anti-VEGF therapies exacerbate neuronal cell death (Boia et al, 2020). Engineered zinc finger proteins (ZFPs) that upregulate multiple forms of VEGF in their natural, endogenous, ratios were generated to avoid vascular permeability, edema, and inflammation due to VEGF overexpression.…”
Section: Neuroprotection Approachesmentioning
confidence: 99%
“…Neurotrophic agents have also been tested in ONs ( Boia et al, 2020 ; Figure 2 ). AAV-mediated delivery of Fibroblast growth factor-2, or delivery of the BDNF gene leads to significant increase in RGC survival and reduced RGC axons loss after optic nerve injury or induction of intraocular pressure (IOP) ( Martin et al, 2003 ; Sapieha et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%